Caste in Indian politics / edited by Rajni Kothari - "Kothari, Rajni. (ed.)" (Hyderabad, 2010)
Rejecting the prevailing dichotomy between traditional society and modern polity, Caste in Indian Politics examines their interaction in given community and territorial settings. A critical introduction by Rajni Kothari provides the analytical framework. Of the nine studies that follow, four are based on detailed investigation of individual caste movements and structures and their induction into the political process. The other five focus on the macro dimensions of the political involvement of caste. Each essay tries to bring out the substantial change that has taken place in the inter relationship between the antecedent social structure of Indian and democratic politics and underlies the emerging idiom of social-political behaviour. This second edition has an extended prologue by eminent political scientist James Manor. Manors Caste and Politics in Recent times is an optimistic account of the changes and developments in the interplay of caste and politics over the past four decades. He shows how the diminishing influence of caste hierarchies has had widespread implications for the voting patterns of the jati-clusters (caste groups). Taking up the debate where Kothari and other contributors had left it, Manors new chapter makes this seminal collection truly contemporary. The volume will be of interest to students and scholars of political science.
Keywords: Caste and politics-India